2015
DOI: 10.1103/physreva.91.023633
|View full text |Cite
|
Sign up to set email alerts
|

Superfluidity of a pure spin current in ultracold Bose gases

Abstract: We study the superfluidity of a pure spin current that is a spin current without mass current. We examine two types of pure spin currents, planar and circular, in spin-1 Bose gas. For the planar current, it is usually unstable, but can be stabilized by the quadratic Zeeman effect. The circular current can be generated with spin-orbit coupling. When the spin-orbit coupling strength is weak, we find that the circular pure spin current is the ground state of the system and thus a super-flow. We discuss the experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Both adiabatic and sudden preparation was carefully considered, and it was demonstrated that this state is stable for sufficiently small spiral wave vectors. However, despite the recent observation of a (quasi)condensate of magnons [25,26], few studies have been devoted to spin superfluidity in ultracold spinor gas [27][28][29][30], even though this phenomenon has played a prominent role in liquid helium systems [31]. Furthermore, the interplay of mass and spin superfluidity has not been addressed in the ultracold-atom context to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Both adiabatic and sudden preparation was carefully considered, and it was demonstrated that this state is stable for sufficiently small spiral wave vectors. However, despite the recent observation of a (quasi)condensate of magnons [25,26], few studies have been devoted to spin superfluidity in ultracold spinor gas [27][28][29][30], even though this phenomenon has played a prominent role in liquid helium systems [31]. Furthermore, the interplay of mass and spin superfluidity has not been addressed in the ultracold-atom context to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…A condensate with a homogeneous spin current can be described as Ψ = (ψ 1 , ψ 0 , ψ −1 ) T = n 2 (e ik0x , 0, e −ik0x ) T , where ψ 1,0,−1 denote the wave functions of the m z = 1, 0, −1 spin components, respectively, and the spin flow velocity is v r = 2 k 0 /m. The Bogoliubov analysis of this spin-current-carrying state yields a transverse magnon mode, δΨ ∝ (0, e ikx , 0) T , with energy spectra of E k = ( k + q )( k + q + 2c 2 n) [25,41], where k = 2 k 2 /(2m) is the single-particle spectrum and q = |q|− k0 . The gap energy is given by ∆ g = q (q + 2c 2 n) for k = 0, and it decreases with increasing k0 .…”
mentioning
confidence: 99%
“…For instance, since decoherence is such a formidable obstacle to building a quantum computer and, at the same time, we cannot use quantum backups to protect quantum information against this decoherence, considerable effort has been devoted to protecting the stored information by way of quantum error correction [4][5][6].Given these no-go results, it is natural to ask how well one can do when settling for approximate cloning or broadcasting. Numerous theoretical and experimental works have investigated such "approximate cloning machines" (see [7][8][9][10][11][12][13][14][15][16] and references therein). These cloning machines can be of great help for state estimation.…”
mentioning
confidence: 99%
“…Given these no-go results, it is natural to ask how well one can do when settling for approximate cloning or broadcasting. Numerous theoretical and experimental works have investigated such "approximate cloning machines" (see [7][8][9][10][11][12][13][14][15][16] and references therein). These cloning machines can be of great help for state estimation.…”
mentioning
confidence: 99%
See 1 more Smart Citation